Karakteristik Komponen Gizi, Antioksidan, dan Respon Organoleptik Bubur Jagung Tradisional Gorontalo dengan Ekstrak Daun Kersen (Muntingia calabura L.) - Lisna Ahmad; Suryani Une; Yoyanda Bait (agriTECH, 2018)
Traditional food products are no longer attractive to the public, so it needs innovation to ensure that the products have a functional value. The aim of this research is to produce fortified cornmeal with kersen (Muntingia calabura L.) leaf extract which has high antioxidant activity and consumer demand of organoleptics. This research used a completely randomized design with single factor at 6 treatment levels, soaking grits of corn on cherry extract with 0%; 10%; 20%; 30%; 40%; and 50% concentrations. The results of nutrient analysis showed that protein contents ranged from 7.59% – 8.93%; fat 0.53%–0.96%; ash content 0.05%–0.12%; water content 11.6%–13.37%; and carbohydrate 77.24%–78.91%. The result of antioxidant activity showed that the higher concentration of kersen leaf extract added the higher also the antioxidant activity of fortified cornmeal, between 11.85–36.17%. Based on panelists’ organoleptic test, most gave neutral response to like slightly for color, texture, aroma and overall grits, while for the panelists, while for taste they gave dislike slightly response.